Reconversión tecnológica del motor generador DEUTZ F3L912 para la industria láctea Lácteos Latacunga. - Fernández Balarezo, Mario Sebastián. (2021)
Diesel generators can be defined as devices that use mechanical energy to generate electric current continuously. This project's purpose is to develop a digital variable tracking, and triphasic generator set control system. The control process consists of: Turning on/off the triphasic generator set, generated load connection and disconnection; also, variables operation measurements such as generator set function speed, internal combustion engine temperature function and generator internal windings, output voltage, same as acceleration automatic adjustment trough PID acceleration control. A system design made up of micro-controlled modules that can capture and visualize the most relevant variables within the generator set for the device's safe maintenance and operation. Resulting in a 14% fuel consumption saving for each KWh of the generation that in the long term will represent a saving for the industry by decreasing workforce, moreover the implementation of electro-mechanics devices that will promote industrial competitiveness.